The Use of Affixation and Its Errors on BIPA Level 5 Learners' Assignments at the Indonesian Embassy In Lisabon, Portugal - Loren, Fabio Testy Ariance; Silvia Berliana; Asri Lolita; Shenglan Zhou (UIN Raden Mas Said Surakarta, Indonesia, 2024)
This research discusses the affixation found in the weekly assignments of Indonesian language learners for Foreign Speakers Level 5 at the Embassy of the Republic of Indonesia in Lisbon, Portugal. This study aims to describe the usage and errors of affixation in the weekly assignments of Indonesian language learners for Foreign Speakers Level 5 at the Embassy of the Republic of Indonesia in Lisbon, Portugal. The method used is a qualitative descriptive method. The data in this study consists of forms and errors of affixation. The data collection techniques employed are interviews and documentation techniques. The results of this study include the use of affixation in the form of: 1) Prefixes, 2) Suffixes, 3) Infixes, and 4) Circumfixes. Using prefixes amounts to 317 data points, suffixes to 27 data points, infixes to 1 data point, and circumfixes to 70 data points. Furthermore, the errors in affixation include: 1) Prefixes, 2) Suffixes, and 3) Circumfixes found in the weekly assignments of BIPA level 5 learners at the Indonesian Embassy in Lisbon, Portugal, in 2023. The errors found in the weekly assignments of BIPA level 5 learners at the Indonesian Embassy in Lisbon include 23 errors with prefixes, 7 errors with suffixes, and 2 errors with circumfixes. It is hoped that the results presented will serve as a reference for BIPA instructors to understand which affixations are frequently used and which ones often lead to errors by BIPA learners.